WATERSHED MODELING OF RAINFALL EXCESS TRANSFORMATION INTO RUNOFF - Reza Najafi M. (My University, 2003)
In this paper an attempt is made to present a distributed physiographic conceptual model that uses the principles of flow continuity and momentum. For this purpose, the watershed under study is divided into subwatersheds keeping in view the drainage patterns and characteristics. Then the main tributaries are identified and their drainage areas are delineated to form tributary subwatersheds. The main channel subwatersheds have taken care of the remaining area in the vicinity of the main channel. The kinematic wave theory is applied for the overland runoff computations from these subwatersheds. Further, the overland flows are superimposed onto the main channel. The dynamic wave theory is used to route the flows through the main channel to compute the watershed responses at the outlet. The proposed model is tested onto a natural watershed. The computations were performed for few storm events. Comparison of the significant parameters of the computed and the observed hydrographs shows that the maximum relative error in prediction is 5.8%. Thus, the results are satisfactory. Better results can be obtained when measured rainfall-excess data are available or a more realistic loss index is adopted for rainfall-excess separation.
Keywords: WATERSHED MODELING; CONCEPTUAL MODEL; SURFACE RUNOFF; FLOW ROUTING; DYNAMIC WAVE; KINEMATIC WAVE